Molecular phylogenetics of the Pristimantis lacrimosus species group (Anura: Craugastoridae) with the description of a new species from Colombia - Rivera-Correa, M.; Rivera-Correa, M.; J. M. Daza,; J. M. Daza, (Acta Herpetologica, 2016)
The Pristimantis lacrimosus species group, with 24 species distributed in the Neotropics, is a group of arbo- real frogs commonly inhabiting bromeliads. Previous studies have claimed the group to be monophyletic but few spe- cies have been included in phylogenetic analyses. In this paper, we included ve additional species from the northern Andes in Colombia and tested the monophyly of this phenetic group using genetic data under a Bayesian approach. Our results show that the P. lacrimosus group represents two distant and unrelated clades. Clade “A” is endemic to Colombia while Clade “B” encompasses species distributed in Central America, Ecuador and Peru. For the rst time, we reveal the phylogenetic position of P. boulengeri and a new species is described. e new taxon is most closely related to P. brevifrons from southwestern Colombia with a genetic distance of 4.3% for 16S and 10.6% for COI. Our results suggest, one more time, that morphological similarity among species in the most diverse vertebrate genus not necessarily agree with its evolutionary history and that more e ort in alpha taxonomy needs to be done in order to understand the tremendous radiation of this lineage in the Neotropics.
Centro Jambatu - ID 1576